Fairness in Matching Markets: Experimental Evidence - Tobias König; Dorothea Kübler; Lydia Mechtenberg; Renke Schmacker (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
We investigate fairness preferences in matching mechanisms using a spectator design. Participants choose between the Boston mechanism or the serial dictatorship mechanism (SD) played by others. In our setup, the Boston mechanism generates justified envy, while the strategy-proof SD ensures envy-freeness. When priorities are merit-based, many spectators prefer the Boston mechanism, and this preference increases when priorities are determined by luck. At the same time, there is support for SD, but mainly when priorities are merit-based. Stated voting motives indicate that choosing SD is driven by concerns for envy-freeness rather than strategy-proofness, while support for the Boston mechanism stems from the belief that strategic choices create entitlements.
Keywords: D47; C92; I24; D74; 330; matching markets; school choice; voting; Boston mechanism; sincere agents; justified envy